The Link Between Structural and Functional Brain Abnormalities in Depression: A Systematic Review of Multimodal Neuroimaging Studies - Scheepens, Dominique S.; van Waarde, Jeroen A.; Lok, Anja; de Vries, Glenn; Denys, Damiaan A. J. P.; van Wingen, Guido A. (Frontiers in Psychiatry, 2020)
Abstract Background: A large number of neuroimaging studies has revealed widespread alterations in brain structure and function in patients with depression. Most studies used a single neuroimaging modality to investigate either brain structure or brain function. The link between abnormalities in brain structure and function still remains largely unexplored. Methods: We performed a systematic review and retrieved fourteen studies that combined structural and functional neuroimaging methods to investigate the association between structural and functional brain abnormalities ina depression Results: Four studies reported a negative relation between brain structure and function within the default mode network. That is, compared to healthy controls, reduced gray or white matter integrity was associated with enhanced neural activity or connectivity indepression. Two studies reported a positive relation, two studies reported mixed evidence, and six studies found no link between structural and functional abnormalities. Conclusion: Currently, there is no robust relation between structural integrity and brain function in patients witha depression. Yet, several studies point towards a negative relation within the default mode network. Large-scale studies that combine structural with functional neuroimaging are required to determine the link between structural and functional abnormalities.